2022
DOI: 10.1002/gps.5801
|View full text |Cite
|
Sign up to set email alerts
|

Use of technology by people with dementia and informal carers during COVID‐19: A cross‐country comparison

Abstract: Objectives: Considering the adverse outcomes of COVID-19, it is essential to provide adequate support and care for people with dementia and informal carers.Technology can reduce the distress associated with social distancing rules and the decreased access to in-person services. This study aimed to explore the use of technology and its perceived effects across different settings and countries. Methods:The sample was composed of 127 informal carers and 15 people with dementia from the UK, Italy, Australia and Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 57 publications
2
23
0
Order By: Relevance
“…Taken together, our findings support other qualitative research that has suggested ICT could be beneficial for the well‐being of carers and people with dementia during the pandemic 36,42 . They add to this current knowledge base by outlining how ICT, and to some extent AT, were used by both co‐resident and non‐co‐resident carers from multiple socio‐economic backgrounds to enable them to fulfil different aspects of their caring role and so retain aspects of their social inclusion despite the restrictions.…”
Section: Discussionsupporting
confidence: 84%
“…Taken together, our findings support other qualitative research that has suggested ICT could be beneficial for the well‐being of carers and people with dementia during the pandemic 36,42 . They add to this current knowledge base by outlining how ICT, and to some extent AT, were used by both co‐resident and non‐co‐resident carers from multiple socio‐economic backgrounds to enable them to fulfil different aspects of their caring role and so retain aspects of their social inclusion despite the restrictions.…”
Section: Discussionsupporting
confidence: 84%
“…This study emphasises the value of telehealth in keeping us linked, particularly during the COVID-19 pandemic, and in reducing feelings of isolation and loneliness 1. It also reinforced the benefit of keeping patients and caregivers more informed and improving behavioural symptoms 1.…”
Section: Commentarymentioning
confidence: 64%
“…The COVID-19 pandemic brought to light the need to adopt technology in healthcare systems worldwide due to the need for physical distancing and isolation measures, especially in the older adult group 1 2. Several studies have been conducted on telemedicine services for older adults with cognitive impairment, which have shown benefits such as being an effective, convenient and low-cost option.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 However, some patients are likely to find remote technology less helpful than others. They may lack necessary equipment and reliable internet connectivity, be unfamiliar and uncomfortable with the technology, or have mental disorders such as dementia 5 and schizophrenia 6 that affect their motivation and cognitive functioning making it difficult to participate in remote care. Patients, carers and clinicians may also have concerns about privacy and security.…”
Section: Introductionmentioning
confidence: 99%